Bio-oil production from cotton fabric and plastic waste: influence of pyrolysis time in catalytic co-pyrolysis - Ali Bashah, Nur Alwani; Wan Kamis, Wan Zuraida; Ramli, Muhammad Zahiruddin; Idris, Siti Shawalliah; Kamaruddin, Mohamad Anuar (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
This study investigates the influence of pyrolysis time on product yield and bio-oil quality in the catalytic co-pyrolysis (CCP) of cotton fabric waste (CFW) and polypropylene plastic waste (PPW). The experiments were conducted in a fixed-bed microreactor using a chromium-extracted alumina (15CE) catalyst, with reaction times varied between 15 and 75 min under constant conditions (500 °C, 1:1 CFW/PPW ratio, and 1:1 F/C ratio). The results indicate that pyrolysis time significantly affects bio-oil and gas production. Extending the reaction time to 60 min maximized bio-oil yield, reaching 76.4 %. The minimal variation in char yield across different pyrolysis times suggests that the thermal degradation of the feedstock was completed within the first 15 min of CCP. GC-MS analysis revealed that bio-oil primarily consists of hydrocarbon and alcohol, while the concentrations of acids and sugar-derived compounds decreased, indicating their conversion into valuable fuel and chemical products. At a reaction time of 75 min, the formation of aromatic hydrocarbons increased, accompanied by a reduction in oxygenated compounds. Based on both bio-oil yield and quality, a pyrolysis time of 60 min was identified as the best condition for the catalytic co-pyrolysis of CFW-PPW using the 15CE catalyst, achieving the highest yield while maintaining an acceptable bio-oil quality.